The girl you left behind [large type] - Moyes, Jojo, 1969- (Thorndike Press, 2013)
In 1916 French artist Edouard Lefevre leaves his wife, Sophie, to fight at the front. When her town falls into German hands, Edouard's portrait of Sophie draws the eye of the new Kommandant. As his obsession deepens, she will risk everything in the hope of seeing Edouard again. Nearly a century later, Sophie's portrait is given to Liv Halston by her young husband shortly before his sudden death. Then a chance encounter reveals its true worth . . .